Correspondencia entre Cándido Silva Parrilla y Roberto H. Todd - Silva Parrilla, Cándido; Todd, Roberto H. (My University, 1942)
¿Dónde están enterrados los próceres puertorriqueños?
Keywords: Barceló, Antonio R., 1868-1938; Barbosa, José Celso, 1857-1921; Baldorioty de Castro, Román, 1822-1889; Muñoz Rivera, Luis, 1859-1916; Matienzo Cintrón, Rosendo, 1855-1913; Diego, José́ de, 1866-1918; Betances y Alacán, Ramón Emeterio, 1827-1898; Ruiz Belvis, Segundo, 1829-1867; Hostos, Eugenio María de, 1839-1903